La culture matérielle comme support de la mémoire historique : l’exemple des naufragés de Tromelin - Thomas Romon; Max Guerout (In Situ)
The shipwreck of l’Utile, on the 31st July 1761 on the island of Tromelin, and the fate reserved for its ‘cargo’ of illegally transported slaves, led us to probe the memory of the event, and its evolution in time. This memory is closely related to the presence of material remains, which provide insights into the events. The gradual burial, with time, of the traces left by the castaways erases the evidence of their daily reality. Within the framework of ‘La route de l’esclave and Les anneaux de la mémoire’ archaeological excavations carried out by the Groupe de Recherche en Archéologie Navale, with the collaboration of the Institut National de Recherches Archéologiques Préventives, allowed to uncover the remains of the survivor’s daily lives. These shed new light on the historical reality of this event.